Pretransplant metabolic syndrome and its components predict post-transplantation diabetes mellitus in Chinese patients receiving a first renal transplant - Cai R; Wu M; Xing YF (Dove Medical Press, 2019)
Ruiming Cai,1 Meng Wu,2 Yanfang Xing3 1Department of Organ Transplantation, The Third Affiliated Hospital of Guangzhou Medical University, Guangzhou 510150, Guangdong, China; 2Department of Nephrology, Longyan First Hospital, Longyan 364000, Fujian, China; 3Department of Nephrology, The Third Affiliated Hospital of Guangzhou Medical University, Guangzhou 510150, Guangdong, China Background: Post-transplantation diabetes mellitus (PTDM) remains a major clinical challenge following renal transplant. Identification of pretransplant modifiable risk factors may allow timely interventions to prevent PTDM. This study aims to determine whether pretransplant metabolic syndrome and its components are able to predict PTDM in Chinese patients receiving their first renal transplant.Patients and methods: We conducted a single-center retrospective study of 633 non-diabetic patients receiving a first kidney transplant. PTDM was diagnosed between 1 month and 1 year post-transplant. Multivariable logistic regression and Cox proportional hazards model were applied to detect potential pretransplant risk factors for PTDM.Results: One year post-transplant, 26.2% of recipients had developed PTDM. PTDM patients had significantly higher fasting plasma glucose (FPG) (P=0.026) and body mass index (BMI) (P=0.006) than non-PRDM patients, and lower levels of high-density lipoprotein cholesterol (P=0.015). The presence of metabolic syndrome was an independent risk factor for PTDM, as assessed by multivariable logistic regression analysis (OR 1.28, 95% CI 1.04–1.51, P=0.038) and Cox proportional hazards model (OR 2.75, 95% CI 1.45–6.05, P=0.021). Moreover, both FPG >5.6 mmol/L and BMI >28 kg/m2 (obesity) were able to predict PTDM.Conclusion: Our results suggest that the presence of metabolic syndrome and its components, impaired fasting glycemia and obesity, are independent risk factors for PTDM in Chinese non-diabetic patients receiving a first renal transplant. Interventions aimed at improving pretransplant metabolic syndrome may reduce the incidence of PTDM. Keywords: post-transplantation diabetes mellitus, renal transplant, metabolic syndrome, body mass index, fasting plasma glucose